2004
DOI: 10.1177/112067210401400512
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Cnv Associated with Optic Nerve Drusen Treated with Photodynamic Therapy with Verteporfin

Abstract: Subfoveal CNV is an uncommon complication of OND and excellent anatomic and functional results can be obtained with PDT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 4 publications
0
8
0
1
Order By: Relevance
“…Some investigators have advocated the use of photodynamic therapy with verteporfin as safe and effective for the treatment of CNV associated with symptomatic ONHD 13–15…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators have advocated the use of photodynamic therapy with verteporfin as safe and effective for the treatment of CNV associated with symptomatic ONHD 13–15…”
Section: Discussionmentioning
confidence: 99%
“…Successful treatment of optic disc drusen with CNVM has been reported with surgery, 123; 200 laser photocoagulation, 38 photodynamic therapy, 29; 193 and more recently intravitreal anti-vascular endothelial growth factor (anti-VEGF) agents. 2; 9; 37; 69; 84; 99; 175 Both bevacizumab and ranibizumab have been used successfully in children with CNVM secondary to optic disc drusen as young as five years of age.…”
Section: Treatmentmentioning
confidence: 99%
“…71 PDT with verteporfin can be considered in the pediatric population; several case reports suggest that pediatric patients require fewer re-treatments compared with adult patients to stabilize CNV and achieve an improvement in visual acuity; however, atrophic changes in RPE can occur. 36,65,74,75 In our study, both eyes undergoing surgical removal of CNV (100%) showed improved visual outcome without recurrence. In eyes undergoing surgical removal of subfoveal CNV, Sears et al 17 reported visual improvement in 83.3% eyes and a recurrence rate of 33%; Uemura and Thomas 16 reported visual improvement in 72% and a recurrence rate of 35%.…”
Section: Historic Treatmentsmentioning
confidence: 74%